THE DEVELOPMENT STRATEGY OF CULINARY TOURISM IN INDONESIA AS A POTENTIAL BUSINESS - Rahayu Lestari; Elwisam; Kumba Digdowiseiso; Nguyen Duc Tri; Zaliha Zainuddin (RADJA PUBLIKA, 2024)
The tourism sector offers significant growth potential for business opportunities in the food and beverage industry. The culinary diversity in Indonesia is a valuable asset for establishing a wide range of culinary enterprises. The objective of this research is to assess the present state and prospects of the culinary tourism sector in Indonesia, as well as identify the factors that impact its growth as a viable industry. Additionally, the study aims to discover effective strategies for developing and capitalizing on the potential of the culinary tourism business in Indonesia, while considering the following aspects. Elements of marketing, sustainability, and engagement with the local community. Qualitative methods enable researchers to investigate the perspectives, understandings, and encounters of stakeholders, including industry participants, tourists, and local communities, in order to acquire more profound insights. Findings of the research To establish Indonesian culinary tourism as a lucrative global business opportunity, it is crucial to prioritize comprehensive marketing strategies, promote sustainability, and foster international collaboration. The culinary tourism industry can achieve sustainable growth, equitable economic benefits, and empowerment of local communities by leveraging digital technology, exploring collaboration opportunities with influencers, and implementing sustainable practices.